Childbirth violence-based negative health consequences: a qualitative study in Iranian women - Ziba Taghizadeh; Abbas Ebadi; Molouk Jaafarpour (BMC, 2021)
Abstract Background Violation of mothers' rights during childbirth is a global problem that often silently torments women in many parts of the world. The aim of this study was to explore negative health consequences due to childbirth violence based on mothers' perceptions and experiences. Methods To achieve rich data, an exploratory qualitative study was carried out in 2019 on 26 women with childbirth violence experience who had given birth in hospitals of Ilam, Iran. Data were collected using semi‑structure in‑depth interviews (IDIs) and a purposive sampling. Participants were asked about their experiences and perceptions of negative health consequences due to childbirth violence. Data were analyzed by conventional content analysis based on Graneheim and Lundman approach. MAXQDA (v.18) software was used for better data management. Results Final codes were classified into 9 sub-categories and 3 main categories including maternal and newborn injuries, weakening of family ties, sense of distrust and hatred. These findings emerged the theme: negative health consequences. Conclusions This study broke the silence of abused mothers during childbirth and expressed the perspective of mothers who suffered childbirth violence as a routine phenomenon in maternal care, and a serious threat to the health of mothers, newborns and families. Findings of this study can be a warning for maternity health system, monitoring and support structures as well as health policy-makers to seriously plan to prevent and eliminate this problem.